2020
DOI: 10.14309/ctg.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Animal Study of Combined Intragastric Balloon and Duodenal-Jejunal Bypass Liner for Obesity and Metabolic Disease

Abstract: INTRODUCTION: Endoscopic bariatric and metabolic therapies can potentially reproduce similar gastric and small intestinal anatomic and physiologic manipulations as Roux-en-Y gastric bypass. This proof of concept animal study was aimed to assess the feasibility, safety, efficacy, and impact on gastrointestinal physiology of combined intragastric balloons (IGB) and duodenal-jejunal bypass liner (DJBL) for the treatment of obesity. METHODS: Five Ossabaw pigs were fed a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For instance, one study assessed the efficacy of combined IGB and DJBL in an animal study. 44 The study reported a significantly lower rate of weight gain in the combination group (MD, 0.63 kg) compared with IGB alone and DJBL alone (MD, 1.00 and 0.75 kg, respectively). Other combination therapies could be potentially further studied, namely the conjunction of DMR with either ESG or POSE with the aim of enhancing the metabolic outcomes in patients with high-risk conditions such as T2DM or NASH.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, one study assessed the efficacy of combined IGB and DJBL in an animal study. 44 The study reported a significantly lower rate of weight gain in the combination group (MD, 0.63 kg) compared with IGB alone and DJBL alone (MD, 1.00 and 0.75 kg, respectively). Other combination therapies could be potentially further studied, namely the conjunction of DMR with either ESG or POSE with the aim of enhancing the metabolic outcomes in patients with high-risk conditions such as T2DM or NASH.…”
Section: Discussionmentioning
confidence: 84%
“…A preclinical animal study in pigs showed that the sequential insertion of IGB and DJBL resulted in significantly lower rates of weight gain than baseline, and in numerically lower rates of weight gain compared to the insertion of a single device. 56 The combination of the two devices also showed a trend towards higher postprandial GLP-1 levels. Furthermore, repeated implantation of small intestine-targeted EBMTs is another strategy that can be employed for achieving satisfactory longterm weight loss and metabolic improvement outcomes.…”
Section: Future Directionsmentioning
confidence: 95%
“…Combined implantation of gastric and small intestine‐targeted EBMTs is another promising strategy for improving weight loss and metabolic outcomes. A preclinical animal study in pigs showed that the sequential insertion of IGB and DJBL resulted in significantly lower rates of weight gain than baseline, and in numerically lower rates of weight gain compared to the insertion of a single device 56 . The combination of the two devices also showed a trend towards higher postprandial GLP‐1 levels.…”
Section: Future Directionsmentioning
confidence: 99%
“… 52 After implantation of the DJBL, when weight loss and blood glucose improvement reached the platform stage, adding other endoscopic weight loss technologies is advisable, covering gastric balloons to enhance the therapeutic effect. 53 , 54 Moreover, it is necessary to improve the anchor to mitigate damage to the intestinal wall of the anchor site. Simultaneously, the DJBL should be upgraded to prolong the service time of the device and provide longer-term treatment for patients.…”
Section: Future Prospectsmentioning
confidence: 99%